2007
DOI: 10.1111/j.1365-2621.2006.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential uses of thermally treated olive oil waste

Abstract: The ongoing stricter policy rules on environmental issues, recent changes in consumer towards the environmental effects of food production, and even stricter regulations voted by the European Union towards reduction of the use of natural resources initiated a great amount of research towards improving the thermal waste treatment methodology. The olive oil industry continues to be one of the most heavily polluting ones among the food industries. Along this line, various thermal processes, such as pyrolysis, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 70 publications
0
22
0
2
Order By: Relevance
“…After filtered and dried, the obtained solid can be used for solid fuel due to its high calorific value. Compared to other thermo-chemical conversion methods such as pyrolysis and gasification, the temperature for hydrothermal treatment is much lower (200-350°C for hydrothermal, compared with 450-550°C for pyrolysis and 900-1200°C for gasification) [16,24]. In addition, biomass conversion takes place in a wet environment so high moisture content of feed biomass is not an issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After filtered and dried, the obtained solid can be used for solid fuel due to its high calorific value. Compared to other thermo-chemical conversion methods such as pyrolysis and gasification, the temperature for hydrothermal treatment is much lower (200-350°C for hydrothermal, compared with 450-550°C for pyrolysis and 900-1200°C for gasification) [16,24]. In addition, biomass conversion takes place in a wet environment so high moisture content of feed biomass is not an issue.…”
Section: Introductionmentioning
confidence: 99%
“…Various treatment methods for several agricultural wastes have been reviewed in several papers [16][17][18][19]. For energy application purposes, the methods can be simply divided into thermo-chemical and biological processes [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other thermo-chemical conversion methods such as pyrolysis and gasification, the temperature for hydrothermal treatment is much lower (200-500°C for hydrothermal, compared with 450-550 °C for pyrolysis and 900-1200°C for gasification) [8,9]. In addition, biomass conversion takes place in a wet environment, so high moisture content of feed biomass is not an issue.…”
Section: Introductionmentioning
confidence: 99%
“…savastanoi and Corynebacterium michiganense, while Ramos-Cormenzana et al (1995) indicated that this material can be utilized as fertilizer, growth medium for algae, biopolymeric substance production, bioenergy generation, cosmetics production, and in processes in the food industry. Furthermore, Arvanitoyannis et al (2007) concluded that OPW is currently being utilized in and will have significant potential for the future of biodiesel, carbon, and brick production. Mekki et al (2006) indicated that this material can replace the water used in clay brick manufacturing.…”
Section: Introductionmentioning
confidence: 98%